English Speaker Acquisition of Topic and Subject in Multiple Clause Sentences in Japanese - Shoji, Shinichi (Studia Orientalia Electronica, 2020)
This study investigated native English speakers’ acquisition of the constraint for topic-wa and the preference for subject-ga in multiple-clause sentences in Japanese. The constraint for topic-wa is that the topic-wa cannot appear in certain types of subordinate clauses, and the preference for subject-ga is that the overt subject-ga in a subordinate clause should not overlap the topic for a matrix clause. Two sentence-completion experiments were conducted with native English-speaking participants, who were considered advanced-level Japanese learners, as well as native Japanese-speaking participants (the control group). The results indicated that although English speakers followed the constraint for the topic-wa, they frequently used the topic-wa as non-subject topics (unlike native Japanese speakers) when an embedded subordinate clause intervened between the topic-wa and the rest of the matrix clause. Also, English speakers used the same subject-ga for both subordinate and matrix clauses, unlike the native Japanese speakers’ preference. The outcome implies that English speakers associated the topic-wa with English non-subject topics, and the subject-ga with English subjects.